Corporate Pension Payment System under the Constraints of Cost of Capital: An Empirical Study - Lingbin Shan; Ming Su (Discrete Dynamics in Nature and Society)
Reducing the cost of capital is an effective way to increase stockholders’ wealth and can also constrain the amount of corporate pension payments. This paper, taking the companies listed on A-share market during the year from 2008 to 2019 as samples, examines the influence path and effect of corporate pension on cost of capital. It is different from the research results of Western scholars that, in all the samples, corporate pensions reduce the cost of capital through debt and incentive effects. For labor-intensive enterprises and those whose effective income tax rate is less than zero, corporate pensions fail to reduce the cost of capital significantly. While for capital-and-technology-intensive enterprises, those whose effective income tax rate is more than zero, and those whose financing restraint is more or less than zero, corporate pension is proven to significantly reduce the cost of capital. Innovation performance has a partial mediating effect between corporate pensions and cost of capital.